Exposure assessment of infants to Aflatoxin M1 in breast milk and maternal social-demographical and food consumption determinants - Filipe Bogalho Pinto Ferreira, Fernando (2017)
Mycotoxins are secondary metabolites of fungi that have toxic effects on both humans and animals. Aflatoxins are mycotoxins produced by some strains of fungus, such as Aspergillus flavus and Aspergillus parasiticus. Aflatoxin M1 (AFM1) which can be transmitted to newborns via breast milk, is a hydrolyzed metabolite of Aflatoxin B1 (AFB1) that is ingested along with contaminated food. AFM1 is classified as “possibly carcinogenic agent for Human” (group 2B IARC). The occurrence of AFM1 in maternal milk and the degree of exposure of infants to this toxin were studied. The correlation between the concentration of AFM1 and basic socio-demographic factors and the consumption of certain categories of food was also aimed. Thus thirty milk samples from nursing mothers living in Portugal central region were collected, in 2016, and analyzed using a competitive commercial ELISA kit, in order to determine the presence of AFM1. Thirteen samples (43.3%) contained levels of AFM1 above the detection limit (5ng/L), ranging between 5.1 and 10.2ng/L (7.12±1,89ng/L). Statistical analysis showed a moderated correlation between the maternal consumption of dry fruits (r=0.48) and milk (r=0.4) and the concentrations of AFM1 found in the samples. No other studied determinants, whether socio-demographic (age, weight, height, number of children, period of lactation, educational level, professional activity, residence, characteristics of breastfeeding, the infants’ weight) or dietary (frequency of food consumption) showed a significant statistical influence. AFM1 estimated daily intake (EDI) was higher for younger babies (1.06ng/kg b.w.; <7kg) as compared with the older ones (≥ 7kg; 0.8ng/kg b.w.), which can be explained by the higher consumption versus weight. The hazard index for both groups (<7kg b.w.: 5.3; ≥7kg; 4.0) were far greater than 1.0, which is the value that indicate risk for consumers. The results of this study suggest the need to reinforce surveillance of AFB1 occurrence in food, particularly dry fruits and milk, as a protective measure, not only for adults, but ultimately for nursing infants exposed by lactation. Although AFM1 presents an inferior carcinogenic potency, it is noteworthy that when compared with adults, infants feature a lower capacity of carcinogen biotransformation, a fairly restricted diet and a higher consumption in relation to body weight.